Beyond Waters Archaeology and Environmental History of the Amazonian Inland - Stenborg, Per (GOTARC series A, 2016)
This book is one of the outcomes of the project Cultivated Wilderness: Socio-economic development and environmental change in pre-Columbian Amazonia (http://www.cultivated-wilderness.org/). The project has particularly focused on the previously relatively unknown prehistory of the Amazonian hinterland. Our work has revealed that pre-Columbian settlements in the Santarém region in the State of Pará, Brazilian Amazonas, were not (as formerly often assumed) limited to the vicinities of permanent water courses, such as rivers and lakes. On the contrary, the majority of region's archaeological sites are found in an upland area known as the Belterra Plateau, situated south of the present city of Santarém. Series of radiocarbon and luminescence dates link these sites to an expansion of human settlement occurring during the period A.D. 1300-1500. The period appears to have been associated with major transformations of the prehistoric societies, significant population growth and the development of new types of water management and agriculture. The workshop Beyond Waters: Archaeology and Environmental History of the Amazonian Inland formed part of the IX Sesquiannual Conference of the Society for the Anthropology of Lowland South America (SALSA), held in Gothenburg, Sweden in June 2014. The presenters and participants at the workshop included members of the Cultivated Wilderness-project, as well as partners and colleagues from several countries in Latin America and Europe. The contributions of the present volume span a wide range of subjects and fields, including archaeology, soil science, landscape archaeology, paleobotany, stylistic studies, historical information and digital mediation, which gives the book a broad thematic scope.